1971
DOI: 10.1002/1097-0142(197108)28:2<344::aid-cncr2820280214>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cancer of the prostate

Abstract: This study of the epidemiology of cancer of the prostate was based on a retrospective investigation of 300 patients with cancer of the prostate and 400 controls, a review of the charts of an additional 350 patient with prostate cancer, and a review of the literature. The main etiologic lead to which this study could not contribute is the rarity of clinical prostatic cancer in Japan and its increase among Japanese immigrants in the U.S. However, the low rate among Jewish males in the U.S. seems to be related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
117
3
13

Year Published

1979
1979
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(140 citation statements)
references
References 52 publications
6
117
3
13
Order By: Relevance
“…It seems unlikely that these differences have an entirely genetic basis, since in African blacks this disease is reportedly much less common (Wynder et al, 1971 ; HIigginson & Oettle, 1960). In Rhodesian blacks, for example, cancer rates for all sites combined are higher than for American blacks, but rates for cancer of the prostate are less than half the American rates (Doll et al, 1970).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems unlikely that these differences have an entirely genetic basis, since in African blacks this disease is reportedly much less common (Wynder et al, 1971 ; HIigginson & Oettle, 1960). In Rhodesian blacks, for example, cancer rates for all sites combined are higher than for American blacks, but rates for cancer of the prostate are less than half the American rates (Doll et al, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of male genital cancer, particularly of the testis and prostate, have been less frequent, despite the fact that testicular cancer rates have substantially increased in recent years (Clemmesen, 1968;Petersen & Lee, 1972) and that in the United States the prostate is already the second commonest site of cancer in the male (Cutler & Young, 1975). Prostatic cancer rates have also been reported to be rising in various populations (Wynder et al, 1971;Krain, 1973). In fact, age-adjusted prostatic cancer rates for black males in Los Angeles County are higher than the rates for any other site for either sex or any racial-ethnic group.…”
mentioning
confidence: 99%
“…Later in 2006, another meta-analysis containing 19 studies (Wynder et al, 1971;Ragozzino et al, 1982;Mishina et al, 1985;Thompson et al, 1989;Smith et al, 1992;Steenland et al, 1995;Coughlin et al, 1996;Will et al, 1999;Rosenberg et al, 2002;Tavani et al, 2002;Weiderpass et al, 2002;Coker et al, 2004;Lightfoot et al, 2004;Zhu et al, 2004;Gonzalez-Perez et al, 2005;Rodriguez et al, 2005;Tavani et al, 2005) was published (Kasper et al, 2006). They both showed that diabetic patients have a statistically significant (9% in 2004 and 16% in 2006) decrease in the risk of developing PCa.…”
Section: Diabetes Mellitus Reduces Prostate Cancer Risk -No Function mentioning
confidence: 99%
“…The first meta-analysis including 14 studies (Wynder et al, 1971;Ragozzino et al, 1982;Checkoway et al,…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for and against the first two hypotheses has been presented extensively elsewhere (Wynder et al, 1971; Ross et al, 1979). Support for the third theory comes from a number of epidemiological findings.…”
mentioning
confidence: 97%